AN ENSEMBLE APPROACH OF METAHEURISTIC ALGORITHMS WITH PARABOLIC APPROXIMATION TO OPTIMIZE WELL PLACEMENT PROBLEM - ISLAM, JAHEDUL (2021)
Well placement optimization problem is a non-convex, multimodal, and discontinuous optimization problem. In previous research, classical and non-classical optimization techniques were used to solve well placement optimization problem. However, these approaches cannot always find the best solutions as they cannot adjust themselves according to reservoirs. However, the ensemble algorithm often changes search strategies and adds an algorithm based on their success, which makes it more reliable on multimodal optimization problems. Hence, in this thesis, the concept of the parabolic approximation-based ensemble algorithm is utilized to tackle the computationally expensive multimodal well placement optimization problem.